Parents and viewpoints: online learning during the Covid-19 pandemic - Muhamad Galang Isnawan; Essa Eqal Almazroei; Evana Gina Shantika; Indrawati; Muh. Rusmayadi; Samsuriadi (Nashir Al-Kutub Indonesia, 2023)
Parents play an important role during online learning during the Covid-19 Pandemic. However, there are still not many studies that examine parents' perspectives regarding online learning. Therefore, this study aims to examine the perspective of parents regarding the problems experienced by students during online mathematics learning. Participants in this study were 47 parents of students whose ages ranged from 35 to 50 years. The instrument used was an interview guide in the form of a semi-structured interview. Data were analyzed using NVivo-12-assisted thematic analysis. The results of the study show that parents think students have problems in terms of low understanding of math material and children learning less than optimally while at home. However, some parents also revealed that there were no obstacles during online learning during the Pandemic. The results of this study then recommend that parents immediately provide information to the teacher when they find that children cannot solve problems and parents cannot help children in solving these math problems.